The Initiation Study on the Gold Potential Resources at West Coast Area in Lampung Province, Indonesia - Akroma Hidayatika; Suharno; Rahmi Mulyasari; Hesti; Idabagus S Yogi; Arif P Prabowo; Syamsurijal Rasimeng (Journal of Engineering and Scientific Research, 2022)
Gold mineral (Au) is formed due to an increase in the residual solution of magma deposited at high temperature and pressure. This study aims to estimate the potential of gold minerals in the west coast area in Lampung Province. This initiation study was using a geophysical resistivity model. Based on geological data, gold minerals in the West Coast are classified as epithermal hydrothermal deposits in the form of low sulfide quartz veins. The results of the subsurface interpretation were identified as a gold mineralization zone associated with the rock in the form of volcanic rock which has a resistivity value of 400?.m. The source rock volume has been estimated at 130,000 m3 and ?133,000 m3. So that the Au mineral content in the study area is estimated at 0.5-2.09 tons. A future study should be conducted in relation to the development of gold mining industry in Lampung West Coast area, that may integrate more engineering experts.